Grain production and tannin contents on lines of Cajanus cajan (Pigeon pea) in the humid tropic of México - Jarillo, J.; Castillo, E.; Valles, B.; Hernández, R. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2012)
Three trials were conducted between 1985 and 1989 in a site with a hot humid climate, in order to estimate the grain production potential of pigeon pea along with its nutritive value. In the first trial, using a native ecotype there were significant interactions between sowing date and the linear (P â‰¤ 0.0128) and quadratic (P â‰¤ 0.0228) effects of sowing rate. Maximum grain yields were obtained at 18750, 25132 and 26971 hills/ka for the June, August and September 1985 sowings, respectively. In the second trial, the effect of genotype was highly significant (P â‰¤ 0.005) upon grain yield. Mean grain yield was 2451 Ó 492 kg/ha, and range varied from 1211 to 4401 kg/ha. The third trial also showed a highly significant effect of genotype on grain yield (P â‰¤ 0.0050). Average yield was 3105 Ó 896 kg/ha and range went from 574 to 4262 kg/ha. Proximate analysis showed the following figures for trial three: dry matter, 86.4-88.6%; ash, 4.3-5.3%; other extract, 0.6-1.4%; crude fiber, 4.1-6.8%; crude protein, 18.6-27.0%; and nitrogen free extract, 56.3-69.5%. Tannins, as tannic acid, ranged from 0.13 to 0.85%. The effect of genotype was also highly significant (P â‰¤ 0.0001) upon hundred seed weight (32.6 Ó 1.7g), seed number per pod (4.2 Ó 0.4), days to first (117 Ó 8) and 50% (149 Ó 3) flowering, and 75% of ripe pods (168 Ó 3). Plant height ranged from 1.4 to 3.2 m. It was concluded; August was more efficient due to high yield with fewer plants/ha, the plant height was strongly afected by sowing date; the best material in trial two was ICPL-365 (4400 kg/ka); In the trial three lines, with good production included ICPL-6997 and ICPL-265 the local material had performed better (4070 kg/ha) than in trial two; that there is a high potent; al for production of nutritive grain in this specie for environmental conditions described.